Pottery Discoveries at the Penanggootu Site, East Kolaka Regency, Southeast Sulawesi: A Study of Form, Decorative Varieties, and Technology - Sabri, M; Syah, Muh. Ardian; Suryanto, Suryanto (Titian: Jurnal Ilmu Humaniora, 2026)
Archaeological research in East Kolaka Regency, Southeast Sulawesi, remains limited, particularly in the Mendoke Mountain region. This study reports the discovery of pottery fragments from the Penanggootu Site and aims to examine their typological diversity, as well as stylistic and technological attributes. Employing a qualitative-descriptive approach, the research encompasses stages of data collection, processing, analysis, and interpretation. The results reveal a range of vessel forms, including cooking pots, bowls, and jars. Motif analysis indicates the continuity of an early pottery tradition alongside a high degree of visual complexity, suggesting the intergenerational transmission of technical and artistic knowledge. These findings contribute new insights into the dynamics of ancient cultural development in the Mendoke Mountains and underscore the significance of this area as an important cultural landscape that has remained largely overlooked in regional archaeological and historical studies. Abstrak Kajian arkeologis di Kabupaten Kolaka Timur, Sulawesi Tenggara, hingga kini masih relatif terbatas, khususnya pada wilayah Pegunungan Mendoke. Penelitian ini melaporkan temuan fragmen gerabah dari Situs Penanggootu dan bertujuan mengkaji keragaman tipologi, serta aspek stilistik dan teknologi pembuatannya. Penelitian dilakukan melalui pendekatan kualitatif-deskriptif yang meliputi tahapan pengumpulan, pengolahan, analisis, dan eksplanasi data. Hasil penelitian menunjukkan variasi bentuk gerabah berupa periuk, mangkuk, dan kendi. Analisis motif mengindikasikan keberlanjutan tradisi gerabah tua yang berpadu dengan tingkat kompleksitas visual yang tinggi, mengisyaratkan adanya transmisi pengetahuan antargenerasi. Temuan ini memberikan kontribusi baru terhadap pemahaman dinamika budaya kuna di Pegunungan Mendoke serta menegaskan posisi wilayah ini sebagai lanskap budaya penting yang selama ini terabaikan dalam kajian arkeologi dan sejarah regional.